1992
DOI: 10.1242/dev.114.2.521
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factor during embryonic angiogenesis and endothelial cell differentiation

Abstract: Vascular endothelial growth factor (VEGF) is a secreted angiogenic mitogen whose target cell specificity appears to be restricted to vascular endothelial cells. Such factors are likely candidates for regulatory molecules involved in endothelial growth control. We have characterized the murine VEGF gene and have analysed its expression pattern in embryogenesis, particularly during brain angiogenesis. Analysis of cDNA clones predicted the existence of three molecular forms of VEGF which differ in size due to het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 968 publications
(42 citation statements)
references
References 48 publications
0
41
0
1
Order By: Relevance
“…Both VEGFR-1 and VEGFR -2 are confined to endothelial cells during embryonic development. 16,17 VEGFR-2 is exclusively localized on endothelial cells, hence playing an important role in endothelial cell differentiation and vasculogenesis. 18,19 VEGFR-3 primarily regulates the development and regulation of the lymphatic system.…”
Section: Resultsmentioning
confidence: 99%
“…Both VEGFR-1 and VEGFR -2 are confined to endothelial cells during embryonic development. 16,17 VEGFR-2 is exclusively localized on endothelial cells, hence playing an important role in endothelial cell differentiation and vasculogenesis. 18,19 VEGFR-3 primarily regulates the development and regulation of the lymphatic system.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, m6A methylation affects bone formation through blood vessels. Previous studies have found that vascular endothelial growth factor (VEGF), including three homologous spliced variants, 120, 164, and 188, promote angiogenesis and osteogenesis (Breier et al, 1992;Wallner et al, 2015;Hu and Olsen, 2016;Tong et al, 2019). Tian et al (2019) illustrated that knockdown of METTL3 reduced the expression of VEGFA (VEGFA-164 and VEGFA -188).…”
Section: Regulation Of M6a Methylation On Bone Marrow Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Several recent observations have indicated that VEGF, as a secreted and specific mitogen for endothelial cells, may be one of the major angiogenesis inducers in vivo. For example, the expression of VEGF and its receptors accompanies angiogenesis associated with embryonic development (Breier et al, 1992) and hormonally regulated reproductive cycles (Shweiki et al, 1993). Further, in addition to promoting the growth of vascular endothelial cells and increasing vascular leakage, VEGF also induces several proteolytic enzymes including interstitial collagenase, urokinase-type plasminogen activator, and tissue-type plasminogen activator (Pepper et al, 1991).…”
mentioning
confidence: 99%